Multidimensional screen exposure and its impact on psychological well-being in toddlers - Luo, Sha; Guo, Wenjie; Chen, Hao; Zhu, Yidong; Zhu, Guowei; Jia, Yingnan (Frontiers in Public Health, 2024)
ObjectivePrevious studies have indicated a link between screen exposure and children’s mental health, but with the emergence of new screen media and a rise in screen content, uncertainties have grown. Our aim was to investigate the impact of screen use on psychological issues in 2- to 3-year-old children, considering screen time and types of screen media and content.MethodsThis cross-sectional study included participants from Shanghai, China, from February to July 2023. Screen use information was collected from children’s caregivers via online questionnaire. Psychological difficulties of children were reported by parents using the Strengths and Difficulties Questionnaire (SDQ).ResultsAmong the interviewed children, 15.9% had an average daily screen time exceeding 1 hour (h). 52.1% of them viewed inappropriate, non-child-directed screen content, 37.6% were mainly exposed to educational content, and 18.9% watched more fast-paced screen content than slow-paced content. Multivariate regression analysis revealed that the use of mobile phones (β = 1.16, 95% CI: 0.14, 2.18), virtual reality (VR) devices (β = 2.57, 95% CI: 0.62, 4.53) and computers for more than 30 minutes (min) per day (β = 2.15, 95% CI: 0.99, 3.30) were related to higher SDQ difficulty scores. Watching more fast-paced (β = 1.58, 95% CI: 0.80, 2.35) and more noneducational screen content (β = 1.01, 95% CI: 0.35, 1.66) were also associated with increased difficulty scores.ConclusionThe amount of time spent using computers, mobile phones and VR devices and the proportion of exposure to noneducational content and fast-paced content were significantly associated with psychological problems among 2- to 3-year-old children.